Two level routing method with priority link resource allocation balancing in software defined telecommunication network - Lemeshko, O.V.; Nevzorova, O.S. (Radiotekhnika, 2018)
Two-level routing method with priority link resource allocation balancing in software defined telecommunication network is proposed. The proposed method is based on the use of a flow-based mathematical model, which allowed providing a coherent solution of routing and link bandwidth allocation. On the other hand, the basis of the proposed method is the interaction prediction principle of the theory of hierarchical multi-level control system, which allowed the introduction of a two-level hierarchy of calculations: the lower level was responsible for calculating routing variables, and the upper level was responsible for the link resource allocation. The numerical example confirms the correspondence of the method to optimal solutions for the finite number of iterations. Also, due to the use of the interaction prediction principle, the solution of the problem of recalculating routes and the order of link resource allocation can be completed on an arbitrary iteration, and the resulting solution will be permissible and meet all the conditions and limitations.